Escaping from revulsion - disgust and escape in response to body-relevant autobiographical memories. Issue 2 (7th February 2022) - von Spreckelsen, Paula; Wessel, Ineke; Glashouwer, Klaske A.; de Jong, Peter J.
ABSTRACT: The term Repulsive Body Image (RBI) refers to a schematic construct combining body-directed self-disgust and other negative body image features, that is assumed to bias information processing, including autobiographical memory retrieval. When specific memories about the own body are retrieved, intense self-disgust may arise and trigger urges to escape from those memories. We asked 133 women with high (HRBI ; n = 63) and low (LRBI ; n = 70) levels of habitual body-directed self-disgust to recall autobiographical memories in response to 11 concrete body-related cue words in a minimal instructions Autobiographical Memory Test (AMT). Despite an overall low level of memory specificity, we found that RBI levels were associated with stronger disgust reactions and stronger motivations to escape from body-related memories. In addition, disgust reactions to body-related memories accounted for the association between habitual levels of self-disgust and urges to escape from these memories. Thus, the findings indicated that women with body image concerns showed disgust-based urges to escape from body-related memories. This disgust-based urge to avert from body-related autobiographical memories might counteract the correction of an RBI, thereby contributing to the persistence of body image concerns and associated psychopathology.